Langues de France et Charte européenne des langues régionales ou minoritaires: inventaire critique des arguments anti-ratification (2014-2015) [Languages of France and the European Charter for Regional or Minority Languages]. (22nd December 2016) - Roger, Geoffrey; de Bres, Julia
Abstract : The deliberations in France surrounding the potential ratification of the European Charter for Regional or Minority Languages (from January 2014 to October 2015) resulted in a national debate unheard of since 1999, providing new insight into resistance towards promoting these languages in the public space. Despite a recent survey claiming that 'the ideological barriers on this issue have now almost disappeared', the virulent arguments opposing ratification eventually triumphed in the Senate. Basing ourselves on comments published in the media by a range of opponents to ratification of the Charter, we review here the various ideological strategies used to preserve the linguistic status quo in France and to maintain the supremacy of French.